Amsacrine suppresses matrix metalloproteinase-2 (MMP-2)/MMP-9 expression in human leukemia cells - Liu, Wen-Hsin; Chen, Ying-Jung; Chien, Jen-Hung; Chang, Long-Sen (Journal of cellular physiology, 2014)
This study explores the suppression mechanism of amsacrine (4‐(9‐Acridinylamino)‐N‐(methanesulfonyl)‐m‐anisidine hydrochloride) on matrix metalloproteinase‐2 (MMP‐2) and MMP‐9 expression in human leukemia cells. Amsacrine attenuated cell invasion with decreased MMP‐2/MMP‐9 protein expression and mRNA levels in U937, Jurkat, HL‐60, K562, KU812, and MEG‐01 cells. Moreover, amsacrine reduced both MMP‐2/MMP‐9 promoter luciferase activity and MMP‐2/MMP‐9 mRNA stability in leukemia cells. Studies on amsacrine‐treated U937 cells revealed that amsacrine‐elicited ROS generation induced JNK and p38 MAPK activation but reduced the phospho‐ERK level. Amsacrine‐induced ERK inactivation and p38 MAPK/JNK activation were demonstrated to suppress MMP‐2/MMP‐9 promoter luciferase activity and promote MMP‐2/MMP‐9 mRNA decay, respectively. p38 MAPK/JNK activation led to up‐regulation of protein phosphatase 2A catalytic subunit α (PP2Acα) in amsacrine‐treated U937 cells. Okadaic acid (PP2A inhibitor) treatment increased MMP‐2/MMP‐9 mRNA stability in amsacrine‐treated cells, whereas PP2Acα over‐expression increased MMP‐2/MMP‐9 mRNA decay. Amsacrine‐induced MMP‐2/MMP‐9 down‐regulation was also related to PP2Acα up‐regulation on Jurkat, HL‐60, K562, KU812, and MEG‐01 cells. Collectively, our data indicate that amsacrine induces MMP‐2/MMP‐9 down‐regulation via simultaneous suppression of genetic transcription and mRNA stability in human leukemia cells. J. Cell. Physiol. 229: 588–598, 2014. © 2013 Wiley Periodicals, Inc.